Alleviating upstream congestion by using MSBPCCP in distributed networks. (2015) - Dhage, Sudhir N.; Meshram, B.B.
The congestion is one of the major challenge in wireless sensor network (WSN). Congestion occurs due to bufferoverflow, channelcontention, packetcollision, reportingrate, may be dynamic time varying wireless channel condition. Its causes overall channel quality to degrade, raise packet loss which lead to buffer drops and increased delays and consume excess energy. Therefore, it needs to be control the congestion in WSN to support qualityofservices and extend lifespan of system. Hence, to address this challenge, we proposed an efficient protocol which mitigate congestion and allocate appropriate sourcerate to eachnode in WSN. The proposed protocol is modified SB prioritybased congestion control protocol (MSBPCCP) to avoid an upstream congestion in WSN. With the help of ratio of packet interarrivedtime along with packetservicetime, PCCP measure the congestion level/degree. Secondly, it creates priorityindex based on importance of eachnode. Along with congestiondegree and priorityindex MSBPCCP control upstream congestion. The MSBPCCP may avoid packets drops due to traffic congestion and improve the network throughput by providing the better quality of services.